Effect of oral tranexamic acid on erythema index in patients with melasma. (30th October 2020) - Nguyen, Jennifer; Rajgopal Bala, Harini; Ross, Angelique; Wong, Celestine C; Paul, Eldho; Rodrigues, Michelle
Abstract: Melasma is a common disorder of hyperpigmentation that presents a therapeutic challenge for clinical dermatologists. The pathogenesis is complex, but previous studies have demonstrated vascular proliferation is a key factor in the development of the classic hyperpigmented patches. Studies have revealed reduction of erythema by oral tranexamic acid; however, there has been no direct comparison to placebo. This 24‐week randomised placebo‐controlled trial demonstrates oral tranexamic acid may improve erythema in melasma. This mechanism of action may be the reason for the success of tranexamic acid in complex and difficult to treat melasma.